PENGARUH KOMITMEN ORGANISASI, DISIPLIN KERJA, DESKRIPSI PEKERJAAN DAN KOMPENSASI TERHADAP KINERJA PEGAWAI - Sadali, Sadali; Triyono, Triyono (Jurnal Manajemen Dayasaing, 2015)
This study aims to determine the influence of organizational commitment, work discipline, job description and compensation to employee performance se Religious Affairs Office Klaten district. This research is a survey. The data used are primary data by taking a sample of 100 employees of the Office of Religious Affairs se-Klaten district Sampling technicus in this study using random quota sampling method. Data obtained directly from the results of questionnaires. The analytical tool used linear regression. The analysis showed that organizational commitment significantly influence employee performance. Labor discipline significant effect on employee performance. The job description of a significant effect on employee performance. Compensation significant effect on employee performance throughout Religious Affairs Office Klaten district.